Reducing asthma hospitalisations in at‐risk children: A systematic review. (5th August 2021) - Chen, Katherine Y H; Saxon, Leanne; Robertson, Colin; Hiscock, Harriet
Abstract : Aim: To identify interventions that reduce hospitalisations and improve related outcomes in children at risk of asthma hospital admissions. Methods: Medline, Embase, Pubmed and Cochrane Library search from January 2002 to April 2020. Inclusion criteria: randomised controlled trials of any intervention for children with asthma who are at risk of hospitalisations. Outcomes: hospitalisation (primary outcome), rescue oral corticosteroid use, school absences, quality of life and cost‐effectiveness. Results: Twelve randomised controlled trials were conducted with 2719 participants. Due to heterogeneity of interventions and reporting of outcomes, a meta‐analysis was not conducted. Multi‐modal interventions comprising caregiver education, reduction of home environmental allergens and regular follow‐up reduced hospitalisations, rescue corticosteroid use and improved quality of life. Cost‐effectiveness was not reported. Three studies scored an overall low risk of bias, and nine had some concerns. Conclusion: Multi‐modal interventions can be effective in reducing hospitalisations, rescue oral corticosteroid use and quality of life but cost‐effectiveness is unknown.